Boko Haram: Islamism, politics, security and the state in Nigeria - Pérouse de Montclos, Marc-Antoine (WAPOSO Series, 2014)
This book is the first attempt to understand Boko Haram in a comprehensive and consistent way. It examines the early history of the sect and its transformation into a radical armed group. It analyses the causes of the uprising against the Nigerian state and evaluates the consequences of the on-going conflict from a religious, social and political point of view. The book gives priority to authors conducting fieldwork in Nigeria and tackles the following issues: the extent to which Boko Haram can be considered the product of deprivation and marginalisation; the relationship of the sect with almajirai, Islamic schools, Sufi brotherhoods, Izala, and Christian churches; the role of security forces and political parties in the radicalisation of the sect; the competing discourses in international and domestic media coverage of the crisis; and the consequences of the militarisation of the conflict for the Nigerian government and the civilian population, Christian and Muslim.